Inflammation in preterm and term labor and delivery - Romero, Roberto (Semin Fetal Neonatal Med, 2006)
Inflammation has been implicated in the mechanisms responsible for preterm and term parturition, as well as fetal injury. Out of all of the suspected causes of preterm labour and delivery, infection and/or inflammation is the only pathological process for which both a firm causal link with preterm birth has been established and a molecular pathophysiology defined. Inflammation has also been implicated in the mechanism of spontaneous parturition at term. Most cases of histopathological inflammation and histological chorioamnionitis, both in preterm and term labour, are sub-clinical in nature. The isolation of bacteria in the amniotic fluid, known as microbial invasion of the amniotic cavity, is a pathological finding; the frequency of which is dependent upon the clinical presentation and gestational age. There is a window of time during which it may be possible to detect a ‘molecular signature of inflammation’ by analysis of the transcriptome before histological evidence is observed. This article reviews the role of inflammation in preterm and term parturition. It is possible that modulation of inflammation using anti-inflammatory cytokines, corticoids, antioxidants and/or other factors may complement antibiotic therapy and limit fetal injury.